Biotransformation of Tetrachloroethylene to Vinyl Chloride and Ethylene in Soil and Groundwater - Nagafuchi, Yoshitaka; Hanashima, Masataka; Kitamori, Shigeji; Tagami, Shiro; Tokunaga, Takashi; Sera, Nobuyuki; Matsufuji, Yasushi (Journal of the Japan Society of Waste Management Experts, 1997)
Vinyl chloride (VC) is known to be the most toxic compound among the dechlorination products from tetrachloroethylene (PCE), and is suspected to be carcinogenic. We investigated contaminations of VC in various soils and groundwaters which were originally contaminated with PCE. The presence of VC was detected in several groundwaters, where a number of orange-pigmented bacteria which dechlorinated PCE to cis-1, 2-dichloroethylene (DCE), were found. The addition of groundwater sediments was necessary to convert PCE to VC and finally to ethylene (ET) . This conversion was stimulated by the addition of glucose and cysteine. The complete dechlorination from PCE to ET and the incomplete dechlorination from PCE to DCE were thus demonstrated in the groundwater. Complete dechlorination required a strict anaerobic condition, and PCE (21 mg/l) was totally converted to ET in 16 days at 25°C. These results suggest that facultative anaerobes are involved in the incomplete dechlorination of PCE to DCE. On the other hand, obligatory anaerobes are involved in the complete dechlorination of PCE to ET.